Application of aesthetic principles in the creation of inclusive urban environments - Bulatov, Valerii (Art and Design, 2025)
The development of the modern inclusive urban environment of advanced countries increasingly considers aesthetic principles that help to make the space not only functional and accessible to all, but also aesthetically pleasing, thus achieving internal comfort through aesthetic influence. The purpose of this study was to identify and classify the aesthetic principles of forming an inclusive urban environment at the beginning of the 21st century. The study was based on the analysis of the literature on inclusive design and methods of aesthetic development of urban areas. The study proved that the aesthetics of an inclusive urban environment positively influences the well-being and experience of people with disabilities. It was determined how aesthetic elements can be used to improve navigation, orientation, and safety for people with disabilities. The study explored new and creative ways of integrating aesthetics and inclusivity that extend beyond basic accessibility requirements, creating a more comfortable and attractive urban space. Aspects that help to achieve the optimum combination of practicality and aesthetic appeal were identified, making the inclusive environment convenient for everyone and at the same time preserving its aesthetic value. The study analysed and highlighted the aesthetic principles that are most effective for creating a truly inclusive and functional urban environment. The practical significance of the findings lies in the fact that the use of aesthetically designed solutions, such as contrasting colours, clear navigation, and tactile surfaces can substantially improve orientation and safety for people with various types of disabilities. This contributes to the psychological well-being and sense of belonging of all users, regardless of their physical capabilities.